PENGEMBANGAN BAHAN LITERASI PAI BERBASIS MEDIA SOSIAL - Wirani, Syifa Aulia; Fakhruddin, Agus; Afriatien, Toto Suryana (TARBAWY : Indonesian Journal of Islamic Education, 2020)
Abstract. This research aims at finding alternative solutions for students in order to obtain Islamic religious knowledge iwithout feeling bored, namely by developing Islamic lesson’s into Islamic literacy material by utilizing information technology development, namely the internet, especially Instagram social media. This research uses descriptive analytical methods and researchers become key instruments. The technique of collecting data uses literature studies and visual material studies, as well as data analysis by using content analysis. The results of the study showed that with Islamic literacy uploaded on Instagram social media, students could read Islamic literacy anywhere and anytime. The results of this research found by researchers based on various responses on instagram social media, are that students are more interested in learning material and interested in discussing broader knowledge of Islam apart from the material in the Islamic religious Education book. Abstrak. Penelitian ini bertujuan untuk menemukan alternatif solusi bagi peserta didik agar dapat memperoleh pengetahuan Agama Islam dengan cara yang tidak membosankan yaitu dengan mengembangkan bahan ajar Pendidikan Agama Islam (PAI) berbasis teknologi informasi yaitu internet, khususnya media sosial Instagram. Penelitian ini menggunakan metode deskriptif analitis dan peneliti menjadi instrumen kunci. Teknik pengumpulan data menggunakan studi pustaka dan studi bahan visual, serta analisis data menggunakan analisis isi. Hasil penelitian menunjukkan bahwa dengan adanya bahan literasi PAI yang diunggah di media sosial Instagram peserta didik dapat membaca materi PAI di mana saja dan kapan saja, peserta didik lebih berminat untuk mempelajari materi, peserta didik tertarik untuk membahas materi keislaman di luar materi yang ada di buku PAI.